2008
DOI: 10.1037/0022-006x.76.1.158
|View full text |Cite
|
Sign up to set email alerts
|

Does the use of telemental health alter the treatment experience? Inmates' perceptions of telemental health versus face-to-face treatment modalities.

Abstract: In corrections, where staffing limitations tax an overburdened mental health system, telemental health is an increasingly common mode of mental health service delivery. Although telemental health presents an efficient treatment modality for a spectrum of mental health services, it is imperative to study how this modality influences key elements of the treatment experience. In this study, the authors compared inmates' perceptions of the working alliance, postsession mood, and satisfaction with psychiatric and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
120
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(132 citation statements)
references
References 34 publications
(34 reference statements)
6
120
2
Order By: Relevance
“…Building rapport and establishing a therapeutic alliance in TMH has additional nuance given the potentially negative impact of technology on clinical work, especially when the distant patient community differs culturally and demographically from the clinician's own community. Nonetheless, experienced teleclinicians and preliminary research suggest that clinicians and patients can, and do, establish a therapeutic alliance during TMH treatment that closely approximates, even equals, face-to-face treatment (Ghosh et al 1997;Bishop et al 2002;Cook and Doyle 2002;Bouchard et al 2004;De Las Cuevas et al 2006;Himle et al 2006;Knaevelsrud and Maercker 2006;Modai et al 2006;Morgan et al 2008;Ertelt et al 2010). Only occasionally do patients rate alliance, or rapport, as significantly lower for TMH versus the faceto-face modality (e.g., Morland et al 2010) Overall, the number of studies and enrolled subjects in these studies is not large, methodologies have differed across studies, and most studies have focused on patient ratings.…”
Section: Evidence Base Supporting the Establishment Of Rapport And A mentioning
confidence: 99%
“…Building rapport and establishing a therapeutic alliance in TMH has additional nuance given the potentially negative impact of technology on clinical work, especially when the distant patient community differs culturally and demographically from the clinician's own community. Nonetheless, experienced teleclinicians and preliminary research suggest that clinicians and patients can, and do, establish a therapeutic alliance during TMH treatment that closely approximates, even equals, face-to-face treatment (Ghosh et al 1997;Bishop et al 2002;Cook and Doyle 2002;Bouchard et al 2004;De Las Cuevas et al 2006;Himle et al 2006;Knaevelsrud and Maercker 2006;Modai et al 2006;Morgan et al 2008;Ertelt et al 2010). Only occasionally do patients rate alliance, or rapport, as significantly lower for TMH versus the faceto-face modality (e.g., Morland et al 2010) Overall, the number of studies and enrolled subjects in these studies is not large, methodologies have differed across studies, and most studies have focused on patient ratings.…”
Section: Evidence Base Supporting the Establishment Of Rapport And A mentioning
confidence: 99%
“…In studies without a comparison group, researchers often concluded that users were generally satisfied when engaging in psychotherapy over telemedicine Myers, Valentine, & Melzer, 2008;Simpson, Bell, & Britton, 2006;Simpson et al, 2003;Simpson et al, 2002), and studies that compared VC to in-person psychotherapy reported similar satisfaction levels between the conditions (Cluver et al, 2005;King et al, 2009;Morgan et al, 2008;Nelson, Barnard, & Cain, 2003;Ruskin et al, 2004). When sources of dissatisfaction arose, they primarily involved technical challenges, but such issues appeared to have little impact on overall satisfaction levels (e.g., Cowain, 2001;).…”
Section: Satisfaction (Question 9)mentioning
confidence: 99%
“…In Table 1, the authors summarize the handful of studies that have addressed individual child therapies using videoconferencing (Glueckauf et al 2002;Nelson et al 2006;Bensink et al 2008;Clawson et al 2008;Fox et al 2008;Morgan et al 2008;Shaikh et al 2008;Wilkinson et al 2008;Witmans et al 2008;Mulgrew et al 2011;Storch et al 2011;Himle et al 2012;Nelson et al 2012b;Reese et al 2012;Banitt et al 2013;Davis et al 2013;Heitzman-Powell et al 2014;Hommel et al 2013;Lipana et al 2013;Xie et al 2013;Tse et al 2015). Most studies are interventions for attention-deficit/ hyperactivity disorder (ADHD), but also include a variety of single study examples.…”
Section: Summary Of Evidencementioning
confidence: 99%